REMEDIASI TANAH TERCEMAR TIMBAL (Pb) DAN AKUMULASINYA PADA TANAMAN GUMITIR (Tagetes erecta L.) - Dewi, I G. A. K. S. P.; Sunariani, N. L. G. A.; Suprihatin, I. E. (Jurnal Kimia (Journal of Chemistry), 2022)
Lead (Pb) is a common pollutant found in agricultural soils and often contaminates the plants growing on the soil. One way to reduce the content of heavy metal contamination such as Pb in agricultural soil is through phytoremediation. The purpose of this study was to reduce the content of Pb in agricultural soils. The method used was remediation by planting  gumitir  ( Tagetes erecta L .) plants on the soil added with various concentrations of Pb 2+ . The results showed that before planting with gumitir, the soil A, B, C added with Pb of 100; 200; and 400 mg Pb/kg soil, respectively, having the concentration of 108,97±2,25; 214,18±5,47; and 447,04±4.89 mg/kg, respectively, while on the harvesting time the concentration of Pb was 100,52±1,66; 170,04±2,88; and 397,98±2,24 mg/kg, respectively. The part of the plant that absorbed the highest Pb was the root, which was 47,01±4,52 mg/kg. The effectiveness of Pb absorption by gumitir plants in A, B, and C soils were <50% with TF and BCF values ??< 1, so the mechanism in accumulating lead metal is less effective or called phytostabilization. Keywords : adsorption, effectiveness, lead, remediation,  Tagetes erecta L.